The Role of Digital Innovation in Business Growth - Sofyan, Ade (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to investigate the role of digital innovation in business growth and its relationship with company financial performance through a Systematic Literature Review (SLR) approach. The concept of digital innovation in business, including the factors influencing it, such as organizational transformational maturity, corporate culture, business modeling tools, and digital technology convergence, is examined in depth. Next, analysis is carried out to understand the relationship between digital innovation adoption and company financial performance, taking into account the industry context, company size, and other contextual factors. The results of this research provide valuable insights for business practitioners and academics in understanding the complexity of digital innovation and its impact on business growth and company financial performance.